Corporate governance, profitabilitas, leverage, dan pengaruhnya terhadap pengungkapan sosial dan lingkungan - Dewi, Nurnika Asri (JIFA (Journal of Islamic Finance and Accounting), 2019)
This study aims to analyze the effect of corporate governance, profitability, and leverage on social and environmental disclosure. The data in this study are 40 property, real estate, and building construction companies listed on the Indonesia Stock Exchange during 2014-2016, so there are 120 observational data. The hypothesis in this study was tested using multiple linear regression analysis with the application of SPSS version 23. The results of this study indicate that institutional ownership, audit committee, and leverage have an effect on social and environmental disclosure. Meanwhile, the independent board of commissioners and profitability has no effect on social and environmental disclosure. Keywords : corporate governance. profitability, leverage, Social and Environment Disclosure Index (SEDI) JEL Classification: Q56, C12, G23,G32, G38, O16